Actividad lúdica en el desarrollo del lenguaje oral en los niños del nivel iniciaL de la Unidad Educativa " Luis Felipe Borja". - Guanochanga Llumigusín, Verónica Elizabeth (2021)
The present research work approaches the problem related to the low development of the oral language in the children, this work was carried out with the objective to improve the oral language by means of the playful activity in the children of the initial level “Luis Felipe Borja" school to help in the kid integral development from early age. For this research a quantitative approach was used because it allowed the collection and analysis of data by means of different instruments. Besides proving already existing theories in the research field, the deductive method was used because it started from the observation of the problem until arriving to the proposal. In the objectives that were raised it was possible to prove the theory with the reality to be able to establish the relation between the two variables used in the investigation the playful activity and the oral language development. In addition, it began with the perceptual level since it was possible to explore and describe everything that is defined about the playful activity and the oral language development. It was apprehensive since it allowed us to buy and analyze the results obtained within this research; it was comprehensive since the most relevant aspects found in the research were made known until a solution was proposed. This research is of non-experimental character since the existing theories were not modified. After the application of data collection instruments such as observation cards, surveys and interviews. It was possible to determine the problems that existed. For this reason, was designed a proposal structured by stimulation workshops through playful activities that are articulated with the skills of the early education curriculum, this proposal has been reviewed and validated by experts who consider it an alternative solution and feasible to be applied